Pengaruh PAD, Tax Effort, dan Belanja Modal Terhadap Tingkat Kemandirian Keuangan Daerah - Frijunita, Syafira; Gurendrawati, Etty; Utaminingtyas, Tri Hesti (Jurnal Akuntansi, Perpajakan dan Auditing, 2024)
This research aims to determine the influence of regional own-source revenue (PAD), tax effort, and capital expenditure on the level of regional financial independence. Sampling was conducted using purposive sampling. The analytical technique employed was panel data regression, with a sample size of 34 districts and/or cities. The data used in this study were secondary data obtained from the official websites of districts/cities in Central Java Province. The results of the t-test indicate that PAD has a positive effect on the level of regional financial independence. Tax effort does not significantly affect the level of regional financial independence. Capital expenditure also does not affect the level of regional financial independence. Meanwhile, the F-test results show that PAD, tax effort, and capital expenditure can be used to predict the level of regional financial independence Keyword: PAD, Tax Effort, Capital Expenditure, The Level of Regional Financial Independence